2018
DOI: 10.1080/21568235.2018.1475248
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based policy and higher education quality assurance: progress, pitfalls and promise

Abstract: Evidence-based policy has become a norm in the current policymaking rhetoric, affecting also higher education quality assurance. This article agrees with critics that rigorous ex-post impact studies are highly challenging in the field of quality assurance. Nevertheless, there are alternative ways how evidence can effectively guide quality assurance policies and how evidencebased mentality can be encouraged by government policies. A more realistic view on how evidence informs policies (indirectly and via stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 42 publications
1
26
0
7
Order By: Relevance
“…In order for it to have practical implications, in our opinion research needs to be an inclusive process gathering all stakeholders (participating and making de-cisions regarding HE) who will create common understanding of the dropout phenomenon and the ways to tackle that issue. This is in line with Beerkens's (2018) stance that evidence-based approach in policy making regarding education should be completed with evidence-informed one if we really want evidence to be incorporated in everyday HE practice and contribute to quality assurance.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In order for it to have practical implications, in our opinion research needs to be an inclusive process gathering all stakeholders (participating and making de-cisions regarding HE) who will create common understanding of the dropout phenomenon and the ways to tackle that issue. This is in line with Beerkens's (2018) stance that evidence-based approach in policy making regarding education should be completed with evidence-informed one if we really want evidence to be incorporated in everyday HE practice and contribute to quality assurance.…”
Section: Discussionsupporting
confidence: 74%
“…Како би имало практичне импликације, неопходно је да такво истраживање буде инклузивног карактера и окупи све релевантне чиниоце на нивоу високог образовања (учеснике и доносиоце одлука) који ће кроз тај процес градити заједничко разумевање феомена осипања, али и начине да се њиме ефикасно бавимо. Ово је у складу са Биркенсовим ставом (Beerkens, 2018) да приступ креирању образовних политика који заговара заснованост на подацима (evidence-based) мора бити допуњен приступом заснованим на информацијама (evidence-informed) које дају учесници образовног процеса, на њиховој перцепцији и искуствима, односно на рефлексијама о томе како се подаци из научних истраживања могу на смислен начин применити у њиховој образовној пракси и учинити је квалитетнијом.…”
Section: закључакunclassified
“…For the Indonesian government, issues of quality assurance and quality enhancement have been a significant focus of attention. Despite differences in the size and stage of development of their higher education sectors, many governments have decided that traditional academic controls are inadequate to today's challenges and that more explicit assurances about the quality are needed [8].…”
Section: Quality Assurance In Universitas Kristen Petramentioning
confidence: 99%
“…Many governments around the world have concluded that traditional academic control is not sufficient anymore, and a more explicit form of quality assurance is needed [8]. In order to enhance the quality assurance system, many countries have developed accreditation systems such as Indonesia's National Accreditation Agency for Higher Education (NAAHE), Malaysia's Malaysian Qualifications Agency (MQA), and the Philippines' Commission on Higher Education (CHED).…”
Section: The Role Of Government In Higher Educationmentioning
confidence: 99%
“…At the same time, Beerkens (2018) has considered an approach to quality assurance of higher education, based on a good deal of evidence identified. Consequently, the approach called the "Golden Standard" is a strict experimental evidence of the fact that it is high-quality tools that act as a means of enhancing students' learning.…”
Section: Literature Reviewmentioning
confidence: 99%